Genotypic variation of forage maize (Zea mays L.) hybrids to sources of nitrogenous fertilizer under non-saline and saline conditions - Ibrahim, Muhammad (Pure and applied biology, 2021)
Water shortage and good quality irrigation water are the main alarming issues for forage production of maize crop in the area of arid and semiarid which enforcing the farmers to utilize municipal irrigation and recycled underground brackish water. These constraints reducing the forage yield and resulting into low forage production due to imbalance fertilizer, salinity and solicitation. Nitrogen (N) application is beneficial for the crops in the accordance of its role in crop productivity and nutrient use efficiency. The current study was conducted to study nitrogenous fertilizers role on maize growth under saline conditions. Nitrogenous fertilizers application increased the plant growth parameters in the term of physical para meters like fresh and dry biomass, plant height(cm), leaf area per plant(cm), number of leaves per plant and crude protein (%) under saline conditions. Nitrogen sources application increased the concentration of nitrate (NO3), ammonium (NH4), potassium(K), K: Na ratio and decreased sodium (Na), under saline condition. A significant difference was observed in all three maize hybrids while comparing the genotypic performance, the maize hybrid FH-949 showed the considerable increase in all observed parameters as compared toFH-9 22 and Pak-Afgoe which showed a significant reduction in term of all growth parameter under saline conditions.